2006
DOI: 10.1211/jpp.58.5.0006
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of S-allyl cysteine sulfoxide (alliin) on cardiac marker enzymes and lipids in isoproterenol-induced myocardial injury

Abstract: The present study was designed to evaluate the preventive effect of S-allyl cysteine sulfoxide (SACS) in isoproterenol (ISO)-induced myocardial ischaemia in male Wistar rats. Rats were pretreated with SACS (40 and 80 mg kg(-1) body-weight) for 5 weeks. After the treatment period, ISO (150 mg kg(-1) body-weight) was administered subcutaneously to rats at intervals of 24 h for 2 days. The activities of creatine kinase, creatine kinase-MB, lactate dehydrogenase, aspartate transaminase and alanine transferase were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 33 publications
1
23
0
1
Order By: Relevance
“…Rats were administered ISO at a dose of 150 mg kg −1 body weight dissolved in 2 mL of normal saline subcutaneously twice at an interval of 24 h [10].…”
Section: Induction Of Myocardial Infarctionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rats were administered ISO at a dose of 150 mg kg −1 body weight dissolved in 2 mL of normal saline subcutaneously twice at an interval of 24 h [10].…”
Section: Induction Of Myocardial Infarctionmentioning
confidence: 99%
“…Group I: normal untreated rats given orally 2 mL of saline by gastric intubation daily for a period of 35 days; groups II and III: normal rats treated with SACS (40 mg kg −1 and 80 mg kg −1 , respectively) in 2 mL of saline by gastric intubation daily for a period of 35 days [10]; group IV: rats were subcutaneously injected with isoproterenol in 2 mL of saline (150 mg kg −1 ) once a day for 2 days; groups V and VI: rats pretreated with SACS (40 mg kg −1 and 80 mg kg −1 , respectively) in 2 mL of saline by gastric intubation daily for a period of 35 days and then subcutaneously injected with ISO (150 mg kg −1 ) once a day for two days [10].…”
Section: Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Jennings et al (1986) have shown that inhibition of the sodium pump may precipitate an excess of internal sodium. In this context, it was reported earlier that the levels of FFAs increased in ISO-treated rats (Sangeetha and Darlin Quine, 2006a).…”
Section: Discussionmentioning
confidence: 64%
“…또한 마늘 추출물은 isoproterenol 유발 심근이상 억제, 고지혈증 감소효과를 일으키는 등, 죽상동맥경화와 관련한 여 러 심혈관 질환을 예방하고 치료하는데 효과가 있다고도 알려 져 있다 [2,6,19]. 마늘추출물을 이용한 세포실험결과에서도 콜 레스테롤합성의 중요 조절 효소인 hydroxymethyl-glutarylCoA reductase 억제효과가 관찰되는 등 [8], 마늘의 주요 성분 이 심혈관 기능과 밀접하게 연계되어 있음을 알 수 있다.…”
unclassified